1998
DOI: 10.1029/98wr02093
|View full text |Cite
|
Sign up to set email alerts
|

The sample areas of conventional and alternative time domain reflectometry probes

Abstract: Abstract. We define the sample area in the plane perpendicular to the long axis of conventional and alternative time domain reflectometry (TDR) probes based on the finite element numerical analysis of Knight et al. [1997] and the definition of spatial sensitivity of Knight [1992]. The sample area of conventional two-and three-rod probes is controlled by the rod separation. Two-rod probes have a much larger sample area than three-rod designs. Low dielectric permittivity coatings on TDR rods greatly decrease th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
152
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(160 citation statements)
references
References 16 publications
6
152
0
1
Order By: Relevance
“…The influence zone of the probe is 20 to 30 mm around the rod, and the accuracy of the measured dielectric constant is ±1% (Ferré et al, 1998). The TDR measurement device is a Campbell Scientific TDR100 (Campbell Scientific, Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
“…The influence zone of the probe is 20 to 30 mm around the rod, and the accuracy of the measured dielectric constant is ±1% (Ferré et al, 1998). The TDR measurement device is a Campbell Scientific TDR100 (Campbell Scientific, Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
“…Ferré et al 4 demonstrated that the sensor sampling area increases with both diameter and rod spacing and that two-rod probes have a much larger sampling area than tree-rod designs. Therefore, this large difference in the necessary sample size between the TRIME-EZ and TDR100 with CS605 is attributable to the differing number of rods between these probes 4 . Further, the smaller sample sizes required for the CS615 and CS616 compared with the TRIME-EZ were due to differences in the diameter and spacing of the rods 4 ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Petersen et al 10 reported that the effective sensor sampling area should contain approximately 95% of the electromagnetic energy. However, the distribution of the electromagnetic energy changes greatly depending on the probe designs 4 . Because there is no evidence regarding the effect of changes in the dielectric constant outside the soil sample on the measurement, the ability of these approaches to specify an appropriate sample size for each type of dielectric soil water sensor remains uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations